Collective disputes in the Syrian labor law (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Labor disputes are the focus of attention in various modern labor legislations, and labor disputes appear in the form of individual disputes or collective disputes.The concept of collective labor disputes raises a problem in terms of defining its concept in view of its dangerous repercussions on the labor sector, which makes the study of this topic extremely important in terms of defining and limiting the concept of collective disputes on the one hand, and determining ways to solve them legally in order to avoid their negative effects on the labor establishment and the interests of workers in general. Therefore, this research revolved around two important points, the first is the concept of collective labor disputes and distinguishing them from individual labor disputes, and the second point is represented by examining the methods of settling collective disputes for work consensual, administrative and judicial in accordance with the provisions of the labor law currently in force in Syria. As a result, we reached several points, the most important of which is that the collective dispute is its basic criterion is the collective character of the parties and the collective interest of the workers. Likewise, the legislator made negotiation a compulsory stage before moving on to other amicable ways to settle the dispute through the intervention of the administrative authority. Therefore, when any dispute or disagreement occurs, it must be resolved amicably through collective bargaining. As for the last solution, it is represented by resorting to the method of arbitration, which is binding on both sides, even if it was unfair to one of them.